TERAPI DENYUT ITRAKONAZOL PADA KASUS TINEA UNGUIUM - Kadek Yuda Sujana; IGK Darmada; Luh Made Mas Rusyati (Universitas Udayana, 2014)
Dermatophytosis is a superficial fungal infection on skin, hair, and nail which caused bydermatophyt. Onicomycosis refers to nail infection which caused by fungal dermatophyt,fungal nondermatophyt, or yeast. Dermatophyt that infected the nail called tinea unguium.Diagnosis for tinea unguium based on the microscopic test with KOH 20%, cultureSaboraud’s dextrose agar (SDA) and histopathologic. In this case reported male, 28 years oldwith changed of the color of nail since four years ago. Dermatologic states is located on tenhand’s fingers and ten foot’s fingers which looked like the nail is thickening, there are keratindebris on the distal part of nail with rough end and nail plate looked like picked up. KOH20% test from nail’s scratch founded long hypha and branched. This patient gives treatmentwith Itraconazol dose 200 mg twice a day for one week in one month and repeated for threemonths. The prognosis is good.